Decision-Making with Uncertainty. Issue 6 (2nd December 2020) - Diggle, Peter J.; Gowers, Tim; Kelly, Frank; Lawrence, Neil
Abstract: In emergency situations like the coronavirus pandemic, decisions must be made quickly, with only partial information. But good decisions are still possible using risk–benefit analysis. By Peter J. Diggle, Tim Gowers, Frank Kelly and Neil Lawrence